SYNTHESIS OF NEW ION EXCHANGE MATERIALS ON THE BASE OF EPOXYACRYLATES - Ybraimzhanovа L.K.; Bektenov N.A.; Sadykov K.A. (Academic Scientific Journal of Chemistry, 2020)
The article studies the properties of obtaining anionite based on a triple copolymer of glycidylmethacrylate, styrene and Acrylonitrile and its suction of strontium ions. The composition and structure of the obtained anion was determined by infrared spectroscopy, were also studied basic physicochemical properties of the resulting anion. Anionite, presented on the basis of GMA-ST-ACN, is promising in the field of ion exchange process and is used for the extraction of strontium ions from aqueous solutions in the field of hydrometallurgy. The work is devoted to a review of the preparation of cross-linked polyelectrolytes, the extraction of strontium (II) ions using anionites. The possibilities of obtaining new nitrogen-containing anion exchangers based on a copolymer of glycidyl methacrylate (GMA), styrene (St) and acrylonitrile (ACN) have been studied. The optimal synthesis conditions were found and the physicochemical properties of the ion exchanger were investigated. Methods for the preparation of new anionites based on a copolymer of glycidyl methacrylate (GMA) with polyethylene polyimines (PEI) have been developed.